Relationship Between Scorpion Stings Events and Environmental Conditions in Mainland France. Issue 6 (5th July 2021) - Vaucel, Jules-Antoine; Larréché, Sébastien; Paradis, Camille; Labadie, Magali; Courtois, Arnaud; Grenet, Guillaume; Langrand, Jérome; Tournoud, Christine; Nisse, Patrick; Gallart, Jean-Christophe; Schmitt, Corinne; Torrents, Romain; et al.
Abstract: In the world, the impact of environmental conditions on the number of scorpion events was evaluated in North Africa, Middle East, and the Amazonian region but not in Europe. In mainland France, scorpion species described are Buthus occitanus (Amoreux, 1789), Belisarius xambeui (Simon, 1879) and 4 Euscorpiidae: Euscorpius concinnus (Koch, 1837), Euscorpius italicus (Herbst, 1800), Euscorpius tergestinus (Koch, 1837), and Tetratrichobothrius flavicaudis (De Geer, 1778). We aimed to describe the impact of environmental conduction on the number of scorpion events. For this, a retrospective multi-center study was conducted with data from the French poison control centers files about scorpion events between 1 January 2011 and 31 December 2020. During the study period, 975 incoming calls for scorpion events were recorded and 574 were related to scorpions native to mainland France and Corsica: B. occitanus (n = 86), Euscorpiidae species (n = 222), B. xambeui (n = 1), and undetermined species (n = 265). Cases were mostly reported along the Mediterranean coast, along rivers, and in cities with a trading port. The number of scorpion events was linked to the rivers' water level, rivers' flow, temperature, sunshine, and pluviometry (P < 0.05 for all variables). B. occitanus need warmest and driest environment than Euscorpiidae spp. A link between the severity of the envenoming and climatic condition or seasonality was not demonstrated.